Impact Of Stuttering on Identity Construction in Women: SLP Perspective - Ramzan, Farzana; Ahmed, Muhammad; Saeed, Bareera; Yaqoob, Saba; Anwar Faridi, Tallat (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2022)
Stuttering is a complex communication disorder characterized by involuntary audible or inaudible stops, repetition, prolongations, blocks, and other symptoms. Objective: To find out the impact of stuttering on identity construction in women through perspective of SLP. Methods: It was a cross-sectional study. Convenient sampling technique was used. It was conducted through social media platforms or online survey by using a self-designed questionnaire. Duration of the study was four months from March 2022 to June 2022, after the approval of DRC. Sample size was 179 that were taken based on random sampling. Experienced SLPs were included in this study. Data analysis was done using IBM SPSS 23 version. Method of statistical were employed which include the descriptive analysis like mean, range, standard deviation, and chi square test. Results: According to the study’s findings, stuttering has an impact on every aspect of a woman’s life. Results indicated that 90(50.3%) stutters were anxious in speaking in social situations, 66(36.9%) stutters feel difficulty in interpersonal and social interactions, 57(31.8%) stutters had extra, and unnecessary facial movements and 68(38.0%) stutters feel that stuttering is affecting their academics performance. All of these factors suggest that stuttering has a significant impact on a woman’s identity. Conclusion: It is concluded from present study that stuttering had negative impact in developing identity in women.